Impact evaluation study for Egypt's Takaful and Karama cash transfer program: Part 2: Qualitative Report - ElDidi, Hagar; El-Enbaby, Hoda; Kassim, Yumna; Kurdi, Sikandra; Petesch, Patti; Moataz, Yasmine; Goessinger, Karim-Yassin (International Food Policy Research Institute, 2018)
This qualitative evaluation of the Takaful cash transfer program was conducted between January and April 2018 by a team of researchers trained in qualitative methods. The evaluation sought to further delve into and explain dimensions of the Takaful transfers’ impact on beneficiaries that were previously under-investigated in the quantitative survey. In so doing, the quantitative components’ findings were also further contextualized and clarified. This qualitative component’s main goals, therefore, were to explore the differences between the transfers’ impact on ultra-poor households and households near the threshold, the differences in how the two household types use the transfer, and the impact of the transfers on intrahousehold decision making with special focus on women.